Fun Strategies for Learning Mathematics: Exploring the Potential of Combinatorial Game Theory in Discrete Mathematics - Klinaku, Leutrim; Elumba, Ledy J; Abbas, Nada Mohammed (Interval: Indonesian Journal of Mathematical Education, 2025)
Purpose of the study: This study aims to examine the effectiveness of using combinatorial game theory in discrete mathematics learning to improve students' understanding and interest in learning. Methodology: Using the Mixed Methods approach, quantitative data were collected through a quasi-experimental design with a pretest-posttest control group, while qualitative data were obtained through interviews and observations. The sample consisted of 60 grade XI students divided into experimental and control classes. Main Findings: The results of the analysis showed that the average gain score of students' conceptual understanding in the experimental class (0.68) was significantly higher than the control class (0.32) with a t-test significance value of 0.001 (p < 0.05). In addition, the motivation questionnaire showed an increase in the average score from 2.9 to 4.1 on a Likert scale of 1–5. Novelty/Originality of this study: Qualitative findings reinforce that game-based strategies encourage active participation, collaboration, and positive perceptions toward discrete mathematical theory.